2005
DOI: 10.6090/jarq.39.169
|View full text |Cite
|
Sign up to set email alerts
|

Two Distinct Growth Types for Number of Developed Leaves, Heading Time, Culm and Panicle Lengths, and Internode Length within Near-isogenic Lines of Rice

Abstract: There are two growth types of plants for the number of developed leaves, heading time, and culm and panicle lengths within a population of a homozygous rice cultivar. However, this phenomenon has not been deeply investigated, because of lack of concrete data. Rice breeders and physiologists have paid little attention to it, regarding it as a genetically uncontrollable environmental variation. To study more details of the phenomenon, we grew two near-isogenic lines of rice with each one of the alleles for the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
2
1
0
Order By: Relevance
“…Kuriyama [15] reported that difference in the number of developed leaves among the early and late rice varieties, and decrease of DTH by each of the SD treatments was accompanied by a decrease in the number of developed leaves in each of the photosensitive varieties examined. The results of the present study indicate that the acceleration of heading by Se1-pat (t) observed from the 13.5-h photoperiod to the 10-h photoperiod conditions was accompanied by a decrease in the number of developed leaves in each of LF3 and LF2 (Tables 5 and 6), which is in accordance with the results of Yokoo et al [47]. The delay of heading caused by se-pat from T65wx to LF1 was accompanied by an increase of number of developed leaves in each of the SD and the 13.5-h photoperiod conditions.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Kuriyama [15] reported that difference in the number of developed leaves among the early and late rice varieties, and decrease of DTH by each of the SD treatments was accompanied by a decrease in the number of developed leaves in each of the photosensitive varieties examined. The results of the present study indicate that the acceleration of heading by Se1-pat (t) observed from the 13.5-h photoperiod to the 10-h photoperiod conditions was accompanied by a decrease in the number of developed leaves in each of LF3 and LF2 (Tables 5 and 6), which is in accordance with the results of Yokoo et al [47]. The delay of heading caused by se-pat from T65wx to LF1 was accompanied by an increase of number of developed leaves in each of the SD and the 13.5-h photoperiod conditions.…”
Section: Discussionsupporting
confidence: 93%
“…Yokoo et al [47] indicated that Se1-u increases culm length, which is in accordance with the result regarding the Se1-pat (t) obtained by using LF3 and T65wx. On the other hand, Efx , the combination of Efx and Ef1 , that of Ef1 and m-Ef1 , and all of the three alleles reduced culm length; particularly, ER50 was the lowest.…”
Section: Discussionsupporting
confidence: 82%
“…This region is also reported to contain the Photoperiod sensitivity 1 gene (Se1 = Hd1) (Yano et al 2000). Se1 plays a significant role in photoperiodic flowering, and it also affects internode elongation and culm length during panicle differentiation and heading (Yano et al 2000, Yokoo 2005). Therefore, the longer days-to-heading and panicle length of these two NILs might have been caused by the introgression of Se1 along with Piz-5 and Pi9.…”
Section: Discussionmentioning
confidence: 99%